DEVELOPMENT OF FREQUENCY MODULATED VOCALIZATIONS IN BIG BROWN BAT PUPS - Mayberry, Heather W. (My University, 2011)
Developing bat pups produce distinct vocalizations called isolation calls (I‐calls) that serve to attract the bat’s mother. How individual pups shift their vocalizations from I‐calls to downward frequency modulated (FM) sweeps during development remains unclear. By recording individual bat pups from the day of birth to twenty‐five days postnatal we observed behavioural and bioacoustic (temporal and spectral) changes in pup calls. Temporal characteristics examined were call duration and call rate; spectral characteristics were minimum frequency, maximum frequency, peak spectral frequency, total signal bandwidth, maximum frequency of the fundamental acoustic element and bandwidth of the fundamental. I‐calls were produced only until a certain point in development, after which pups change from emitting long‐duration, tonal I‐calls to downward FM signals and eventually short‐duration biosonar vocalizations. We discovered additional spectral changes in the harmonic structure of pup calls, with the number of harmonic elements decreasing with age. We also recorded pup vocalizations during prolonged separation from their mothers to determine if extended isolation alters the type, number or acoustic structure of emitted vocalizations. Rate of calling was influenced by prolonged separation; younger pups had higher calling rates and called longer than older pups. We also compared temporal and spectral characteristics of spontaneous and provoked calls. We found that provoked calls were more similar to vocalizations produced by younger pups. By documenting the vocal behaviour and acoustic structure of pups calling in different situations, this research provides groundwork for further studies on the ontogeny and development of FM vocalizations in bats and other mammals.
Keywords: Eptesicus fuscus; echolocation; development; morphology; pups; vocalizations; Other Animal Sciences; Other Psychology; Other Animal Sciences